Nicaragua : The Cost of Inadequate Sanitation - Larsen, Bjorn (World Bank, Washington, DC, 2016)
This report examines the social economic impact of inadequate sanitation in Nicaragua. The study on which it is based has been promoted by the Economics of Sanitation Initiative (ESI), led by the Water and Sanitation Program of the World Bank (WSP). The report includes basic information on Nicaragua, records of sanitation in the country and the results of the analysis of the economic impacts on health, water resources, tourism, and other impacts on welfare.